Coaker film rushes : Interview with Mr. Josiah Kearley. Raw footage - Memorial University of Newfoundland. Extension Service (Memorial University of Newfoundland Extension Service, 1970)
Raw footage of an interview with Josiah Kearley about William Coaker. Interview is choppy, it cuts off in spots. -- Coaker Film- Joe Kearley R-10-P/S -- Cam 24-25 -- Coaker Film- Joe Kearley. R-10-P/S -- Cam 24-25 -- Condition: video quality is poor, choppy; ends abruptly.